قرآنی آیات کی روشنی میں معاصر سائنسی حقائق کا تجزیہ - Dr Saddaqat Hussain (البصيرة)
The Quran, being word of God Almighty, stands unparalleled in its eloquence, wisdom, and uniqueness. It surpasses all forms of human expression, demonstrating a profound depth that leaves an impartial observer in awe. This sacred text not only proclaims the oneness of Allah and the prophethood of Muhammad (PBUH) but also inspires advancements in modern science. An unbiased individual, free from stagnation and undue influence of modern scientific dogmas, discovers astonishing truths upon studying the Quran. Despite being revealed over 1400 years ago to an unlettered Prophet in the isolated and culturally limited Arabian Peninsula, the Quran contains references to numerous scientific phenomena. These encompass a broad spectrum of disciplines, including history, geography, physics, astronomy, celestial bodies, biology, medicine, human sensory perception, and the intricate formation of the human body. What sets the Quran apart is that none of its statements about these fields contradict modern scientific discoveries. On the contrary, many facts mentioned in the Quran have been validated by contemporary science, while others continue to inspire further exploration. The Quran’s compatibility with scientific truth serves as a testament to its divine origin and offers humanity a guide for intellectual and spiritual growth. In essence, the Quran not only provides moral and spiritual guidance but also challenges humanity to engage in intellectual pursuits and scientific exploration, bridging the gap between faith and reason. It stands as an eternal beacon for those who seek knowledge, encouraging them to unravel the mysteries of the universe while remaining grounded in the divine wisdom it offers.